Leadership Styles and Communication Skills at Indonesian Higher Education: Patterns, Influences, and Applications for Organization - Udin Udin; Sri Handayani; Ahyar Yuniawan; Edy Rahardja (Organizations and Markets in Emerging Economies, 2019)
The main purpose of this study is to examine the relationships among leadership styles, communication skills, and employee satisfaction and investigate the potential of women in positions of leadership to support the practice of equal employment opportunities in organizations. Data were collected from 200 self-administered surveys using questionnaires administered to employees at three private Islamic universities in Semarang, Indonesia. Regression analysis was used to test the hypotheses. The results show that leadership styles and communication skills have a significant effect on employee satisfaction. However, on the basis of employee perceptions, this study reveals no significant difference in leadership styles and communication skills between male and female leaders.